When proactivity fails: An electrophysiological study of establishing reference in schizophrenia. - Kuperberg, Gina R.; Ditman, Tali.; Perrachione, Arim Choi. (Tufts University. Tisch Library., 2017)
Background: Schizophrenia is characterized by abnormalities in referential communication, which may be linked to more general deficits in proactive cognitive control. We used event-related potentials (ERPs) to probe the timing and nature of the neural mechanisms engaged as people with schizophrenia linked pronouns to their preceding referents during word-by-word sentence comprehension. Methods: We measured ERPs to pronouns in two-clause sentences from 16 people with schizophrenia and 20 demographically-matched control participants. Our design crossed the number of potential referents (1-referent, 2-referent) with whether the pronoun matched the gender of its preceding referent(s) (matching, mismatching) This gave rise to four conditions: (1) 1-referent matching ("…Edward took courses in accounting but he…"), (2) 2-referent matching ("…Edward and Phillip took courses but he…"), (3) 1-referent mismatching ("…Edward took courses in accounting but she…"), and (4) 2-referent mismatching ("…Edward and Phillip took courses but she…") Results: Consistent with previous findings, healthy controls produced a larger left anteriorly-distributed negativity between 400-600ms to 2-referent matching than to 1-referent matching pronouns (the "Nref effect") In contrast, people with schizophrenia produced a larger centro-posterior positivity effect between 600-800ms. Both patient and control groups produced a larger positivity between 400-800ms to mismatching than to matching pronouns. Conclusions: These findings suggest that proactive mechanisms of referential processing, reflected by the Nref effect, are impaired in schizophrenia, while reactive mechanisms, reflected by the positivity effects, are relatively spared. Indeed, patients may compensate for proactive deficits by retro-actively engaging with context to influence the processing of inputs at a later stage of analysis.